Formulasi dan Uji Penetrasi Sediaan Gel Transfersom yang Mengandung Kojyl 3 Amino Propil Fosfat sebagai Pencerah Kulit - Andini, Septia; Jufri, Mahdi; Djajadisastra, Joshita (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2016)
Kojyl 3 APPA is a compound used for skin lightening. Kojyl 3 APPA has a good solubility in water. This causes the hydrophilic nature kojyl 3 APPA difficult to penetrate through the skin. Transfersom is a carrier system that can improve the effectiveness of drug penetration. This study aims to formulate, characterize and evaluate transfersom preparations containing kojyl 3 APPA. Further more transfersom formulated in a gel formulation. Preparation gel was tested its physical stability and in vitro penetration test against non transfersom kojyl 3 APPA. Transfersom gel formulation is physically proven stable at room temperature, low temperature and high temperature storage. In vitro penetration tests showed that kojyl 3 APPA penetration loaded in transfersom gel was 11,16% while for non transfersom gel 8,02%